Normal variation of clinical mobility of the mandibular symphysis in dogs - Minei, Sergio; Auriemma, Edoardo; Bonacini, Serena; Kent, Michael S.; Gracis, Margherita (Frontiers in Veterinary Science, 2023)
Introduction The primary objective of this retrospective study was to document the normal variation of clinical mobility of the mandibular symphysis in dogs, and evaluate possible associations with breed, bodyweight, age, sex, and skull morphology. Secondarily, the radiographic appearance of the mandibular symphysis and possible associations with the analyzed data were also evaluated. Methods Medical records of dogs that underwent anesthetic procedures for maxillofacial, oral and dental evaluation from April 2015 to December 2021 were included. Results 567 dogs of 95 different breeds were included, with a total of 695 evaluations. Body weight ranged from 0.8 kg to 79 kg (median 14.4 kg) and age from 3 months to 16 years and 4 months (median 6 years and 9 months). Clinical mobility was evaluated under general anesthesia using a 0 to 3 scale, in lateromedial (LM) and dorsoventral (DV) directions. The symphysis was radiographically classified as being fused or open. The open symphyses were further radiographically divided in having parallel or divergent margins. At the time of the first evaluation DV mobility was 0 in 551 cases (97.2%) and 1 in 16 cases (2.8%). LM mobility was 0 in 401 cases (70.7%), 1 in 148 cases (26.1%) and 2 in 18 cases (3.2%). There was not a significant change in mobility over time for cases examined more than once (P= 0.76). All cases had an intraoral radiographic examination. 83.8% of the radiographs were included in the statistical analysis. Two symphyses (0.4%) were classified as fused and 473 (99.6%) as open, 355 (74.7%) having divergent margins and 118 (24.8%) parallel margins. Logistic regression models exploring factors that affected DV and LM mobility were statistically significant (P < 0.0001; P < 0.0001), with an increase in LM mobility predicting an increase in DV mobility, and vice versa. An increase in age and in bodyweight was associated with a decrease in mobility. There was no statistical difference in clinical mobility across specific breeds or sexes. Increased probability of a divergent symphysis and increased DV mobility was found to be associated with a brachycephalic conformation. The increase in LM mobility was comparatively higher in small brachycephalic breeds compared with larger brachycephalic breed. Discussion The majority of the cases showed little to no mobility of the mandibular symphysis and radiographically bony fusion can be rarely seen.